Prospects of using peels of Siamese orange young from fruit thinning in waste minimization - Firdausni Firdausni; F. Failisnur; Kamsina Kamsina; Inda Three Anova; Salmariza Sy; Ardinal Ardinal (Jurnal Litbang Industri, 2022)
Siamese orange (Citrus nobilis) is a local citrus that grows in Mount Omeh, Lima Puluh Kota Regency. The quality is improved through thinning which is the process of removing some of the young fruit. Therefore, this research aimed to use young oranges obtained from thinning fruit in the manufacture of essential oils to reduce waste from citrus plants. Orange peel is converted into essential oil through distillation for 6 hours at 90-1000 C. The results showed that the product obtained had a yield of 0.9% (V/V), pale yellow color, volatility with a specific gravity of 0.84%, refractive index of 1.46, 0.67 acid number, solubility in ethanol 1:19 clear, ester number 27, and 0.02 mg/kg Fe content. The socialization of the use of essential oil and hydrosol in soap making to citrus farmers and industrial craftsmen around the Lima Puluh Kota Regency was also performed. The outcome indicate a positive response from the participants and the local government, thereby increasing the commercial value of oranges.